Investigation on progressive collapse resistance of prestressed concrete frames with infilled walls. (January 2023) - Chang, Dong; Zeng, Bin; Huang, Lin-Jie; Zhou, Zhen
Highlights: The equivalent three-bar diagonal bracing model is used to simulate infilled walls. The node coupling model was used to simulate prestressed tendons. Infilled walls improve the anti-collapse capacity of prestressed concrete frame. Infilled walls and beams constitute a kind of truss-beam system together. Prestressed tendons are the main load-bearing components in catenary action. Abstract: The finite element numerical model of prestressed concrete frames with infilled walls (IW-PC frame) is established to investigate the progressive collapse resistance under the failure of middle column. The simulation of infilled walls adopts the equivalent three-strut diagonal bracing model. The method of node coupling is adopted in the simulation of prestressed tendons Then the pushdown analysis of the structure is carried out. Meanwhile, the effects of the parameters of infilled walls and prestressed tendons on the compression arch action and catenary action are studied. The results show that the infilled walls greatly improve the anti-collapse bearing capacity of IW-PC frame. They enable beams to reach peak loads in advance, and transform the axial force of beam and prestressed tendons in advance. It is more conducive to make the prestressed tendons fully stressed, so that the structure can enter the catenary action in advance, thereby improving the bearing capacity.